Immunostimulatory Properties of Chemotherapy in Breast Cancer: From Immunogenic Modulation Mechanisms to Clinical Practice - Zhang, Jinguo; Pan, Shuaikang; Jian, Chen; Hao, Li; Dong, Jie; Sun, Qingqing; Jin, Hongwei; Han, Xinghua (Frontiers in Immunology, 2022)
Breast cancer (BC) is the most common malignancy among females. Chemotherapy drugs remain the cornerstone of treatment of BC and undergo significant shifts over the past 100 years. The advent of immunotherapy presents promising opportunities and may constitute a significant complementary to existing therapeutic strategies for BC. The traditional view of chemotherapy as a cytotoxic treatment that targets proliferation malignant cells has recently been shown as an effective immunestimulus in multiple ways. Chemotherapeutic drugs can cause the release of damageassociated molecular patterns (DAMPs) from dying tumor cells which induce result in long-lasting antitumor immunity by the key process of immunogenic cell death (ICD). Furthermore, Off-target effects of chemotherapy on immune cell subsets mainly involve activation of immune effector cells including natural killer (NK) cells, dendritic cells (DCs), and cytotoxic T cells, and depletion of immunosuppressive cells including Treg cells, M2 macrophages and (myeloid-derived suppressor cells) MDSCs. Current mini-review summarized recent large clinical trial regarding the combination of chemotherapy and immunotherapy in BC and addressed the molecular mechanisms of immunostimulatory properties of chemotherapy in BC. The purpose of our work was to explore the immune-stimulating effects of chemotherapy at the molecular level based on the evidence from clinical trials, which might a rationale for combinations of chemotherapy and immunotherapy in BC.